Part-time pensions and part-time work in Sweden - Eskil Wadensjö (Institute for the Study of Labor (IZA), 2006)
Sweden had a special partial pension scheme between 1976 and 2001. It was one of three part-time pension schemes in the social security system. The other two were a partial early old-age pension, and a partial disability pension. The special partial pension scheme became very popular with a high take-up rate and was criticized for being too expensive. As a part of the decision on the old age pension scheme in 1994, the partial pension scheme was made less generous, and the scheme was totally abolished from year 2001. The other two options for combining work and receiving a pension continue. In this paper the effect on the total number of hours worked of the subsidized part-time pension system is analysed. The analysis indicates that the effect that people continue to work part-time instead of taking an early exit route is larger than the effect that people who would have continued to work full-time until ordinary retirement age instead work part-time
Keywords: 330